Demo Data as Code. - LIMONCELLI, THOMAS A. (Communications of the ACM, 2019)
The article discusses the benefits of automating the process of generating demonstration data, which treats the data as code and supports the need for iteration, collaboration and updates. Topics include the use of scripting languages to create ad hoc functions that act like a language, the ability of a repeatable process to help with enabling delegation, and challenges associated with anonymizing data.